Waqf laws and management - Rashid, Syed Khalid (IIUM Press, 2017)
This book is a thorough and thought-provoking study of waqf laws and management by scholars of very many countries including Malaysia, India, Turkey, Bangladesh, Nigeria, Bosnia-Herzegovina, etc. The millions of awqaf scattered throughout the world are capable of generating income of billions of dollars, but could not do so because of mis-management of governments as well as non-governmental organizations. An effort is made in all the eighteen chapters of this book to discuss and identify measures, both legal and managerial, to achieve good governance of awqaf to make them more productive. The book also contains, for the first time in Malaysia, a comprehensive narration of the statutory waqf Laws of all the States and Federal Territories in Malaysia. Everyone, including lawyers, researchers and waqf administrators, will find it very beneficial.